"Smart environment": problems of social identity. Issue 1 (March 2020) - Krivykh, E G
Abstract: The article describes the humanitarian problems that arise during the implementation of the Smart City project in the real process of transforming spatial environment. The author aims to study the interaction of the sociocultural components of the urban environment and the formation of the social collective identity of the city dweller. The urban environment is analyzed as an architectural and spatial integrity, possessing the properties of conservation and translation of values, creating the possibility of communicative interaction. The author refers to the concept of multiple identity reflecting the complexity and singularity of identification in the new social environment. The novelty of the study lies in the fact that it presents specific examples of creating sociocultural codes that stimulate the formation of social solidarity by instruments of urban development. It is necessary to create in the objective world the image of the Other that is an indispensable component of personal identity. It can be represented by interaction with urban communities, the main places of formation of which are traditionally public spaces. Theoretical reflection has a practical importance, since the paper considers a new type of public spaces combining the high-tech capabilities of the digital environment and the socio-psychological sense of comfort, security and communion with the spirit of the city.